Delayed presentation of pure duodenal atresia in a preterm infant: a rare case report - Soni, Edamakanti Swetha; Singh, Aditya Pratap; Soni, Mayur Shyam; Bhaisare, Shital Narendra (International Journal of Contemporary Pediatrics, 2025)
Duodenal atresia is a rare congenital anomaly that usually presents in the early neonatal period with non-bilious vomiting. We report a preterm male neonate born at 33 weeks of gestation who presented at 17 days of life with persistent non-bilious vomiting since day two. Imaging showed the classical 'double bubble' sign, and contrast study confirmed complete duodenal obstruction. Exploratory laparotomy revealed type III duodenal atresia, for which a duodeno-duodenostomy was performed. The postoperative recovery was uneventful, and the infant was thriving at one-month follow-up. This report emphasizes that even pure type III duodenal atresia can rarely present late, highlighting the importance of high suspicion in preterm neonates with persistent vomiting.